CONVERGING HERMENEUTICAL CURRENTS: EXPLORING A SUBALTERN THEOLOGICAL METHODOLOGY IN INDIA - Felix Wilfred (Perspectiva Teológica)
The article is an attempt to explore how a convergence of Eastern and Western hermeneutical traditions could help develop a theological methodology focused on the cause of the subalterns in India. With this intent, it tries to point out the intersection and resonance between the traditional “dhvani” method of interpretation and some of the contemporary Western hermeneutical currents. With reference to Indian tradition, the article highlights how the art of interpretation not only follows the text but is involved also in the creation of a plurality of texts. The freedom from textual essentialism, which the Indian hermeneutical tradition embodies, allows a lot of space for the subalterns not only to interpret texts from their standpoints but also create new ones, leading to a liberative hermeneutics. In this context, the article studies the convergence of structural and post-structural hermeneutics with classical Indian hermeneutical currents and how they can help the cause of the subalterns and the articulation of a theology from their perspective.